The Effect of Bilingual Ability on Executive Function in Early Childhood: A Comparative Study between Bilingual and Monolingual Children - Husnul Hafidhoh (Journal of Psycho Linguistics, 2025)
This study aims to analyze the differences in executive function between bilingual and monolingual children and identify factors that strengthen or weaken these abilities in the context of bilingualism. The research method used is a qualitative approach with phenomenological design, involving 30 early childhood consisting of bilingual and monolingual groups. Data were collected through in-depth interviews with parents and teachers as well as direct observation of children in play and learning environments. The results showed that bilingual children had better abilities in attention, working memory, cognitive flexibility, inhibitory control, and information processing speed than monolingual children. These findings support the theory that bilingualism strengthens executive functions through the activity of managing two languages that requires high focus and adaptability. In conclusion, bilingual education has the potential to enrich children's cognitive development, especially in enhancing executive functions that are crucial for academic and social success. The implications of this study show the importance of integrating a bilingual approach in the early childhood education curriculum to support more optimal cognitive development.